FACLibras: Uma proposta de ferramenta para avaliação da compreensão da língua brasileira de sinais- LIBRAS por jovens surdos - Freitas, Joice Raquel Lemes de (Universidade Federal de São Carlos, 2022)
The bilingual education model for the deaf defends, among other aspects, the appropriation of the Brazilian Sign Language (Libras) as a first language and that teaching this language is important, especially in dialogic processes, since the more present the language is in the relationships social, the more effective acquisition and learning will be. Thus, we understand the importance of Libras for the school education of deaf people and we know that this refers to several issues. In this study, we intend to investigate a resource for assessing the understanding of Libras, so this research presents the evaluative tool "FACLibras" composed by the children's story "The turtle and the eagle", narrated in Libras, along with a cast of fifteen questions referring to to her. The tool was based on a Spanish survey and the purpose of this procedure is to verify, from the participants' responses, their level of understanding regarding aspects related to Libras. Thus, after a pilot application, it was possible to perceive a great potential of the tool and, on the other hand, that to fully achieve its objectives, FACLibras needed some adjustments. Therefore, the objective of this study was to proceed with the investigation of FACLibras, seeking to improve the presentation of the narrative and the wording of the questions, as well as the multiple-choice alternatives. The specific objectives of the study are: a) to review the videos that comprise the narrative, as well as the questions and alternatives related to it; b) reorganize the tool in a new version, according to the necessary adjustments; c) apply the new version of the tool. The methodological procedures range from organizing a team of specialists to observe and take notes about the material to make the necessary adjustments, to the process of applying the tool to the participants. It was expected that, after adjusting and applying the tool, the results would reveal a sensitivity of the construct and in its final version the tool proved to be sensitive to the variation in age and grade of the participants, indicating its suitability to be used by teachers in the future.

El modelo de educación bilingüe para sordos defiende, entre otros aspectos, la apropiación de la Lengua de Signos Brasileña (Libras) como primera lengua y que la enseñanza de esa lengua es fundamental, sobre todo en los procesos dialógicos, ya que cuanto más presente está la lengua en las relaciones sociales, más eficaz será la adquisición y el aprendizaje. Así, entendemos la importancia de la Libras para la educación escolar de las personas sordas y sabemos que esto se refiere a varias cuestiones. En este estudio pretendemos investigar un recurso para evaluar la comprensión de Libras, por lo que esta investigación presenta la herramienta “FACLibras”, compuesta por el cuento infantil “La tortuga y el águila”, narrado en Libras, junto a quince preguntas referentes a ella. La herramienta se basó en una investigación española y el propósito de este procedimiento es verificar, a partir de como responden los participantes, su nivel de comprensión sobre aspectos relacionados con Libras. Así, después de una aplicación teste, nos demos cuenta del gran potencial de la herramienta y, por otro lado, que para lograr plenamente sus objetivos, FACLibras necesitaba algunos ajustes. Por lo tanto, el objetivo de este estudio fue continuar con la investigación de FACLibras, buscando mejorar la presentación de la narrativa y de las preguntas, así como las respuestas de opción múltiple. Los objetivos específicos del estudio fueron: a) revisar los videos que componen la narrativa, así como las preguntas y alternativas relacionadas con la misma; b) reorganizar la herramienta en una nueva versión, de acuerdo con los ajustes necesarios; c) aplicar la nueva versión de la herramienta. Los procedimientos metodológicos van desde la organización de un equipo de especialistas para observar y tomar notas sobre el material para realizar los ajustes necesarios, hasta el proceso de aplicación de la herramienta a los participantes. Se esperaba que, después de ajustar y aplicar la herramienta, los resultados revelaran una sensibilidad del constructo y en su versión final la herramienta demostró ser sensible a la variación de edad y grado de los participantes, indicando su idoneidad para ser utilizada por profesores en el futuro.
FACLibras: Una propuesta de herramienta para evaluar la comprensión de la lengua de signos brasileña - LIBRAS por jóvenes sordos
FACLibras: A proposal for a tool for assessing understanding of Brazilian sign language - LIBRAS by deaf young people
Keywords: Educação Especial; Ferramenta de avaliação; Compreensão de Libras; Special Education; Assessment tool; Understanding Libras; Educación Especial; Herramienta de evaluación; Comprensión de Libras; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL